In vitro and in vivo characterisation of SARS-CoV-2 wildtype, Beta, Delta and Omicron variants of concern : growth kinetics and viral shedding - Sutherland, Andrew David (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.